A narrative review of glucagon-like peptide-1 receptor agonists prior to deep sedation or general anesthesia - Luigi Vetrugno; Cristian Deana; Andrea Da Porto; Enrico Boero; Valentina Bellini; Daniele Guerino Biasucci; Elena Giovanna Bignami (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Glucagon-like peptide-1 receptor agonists are a class of drugs that mimic a natural incretin hormone released by the intestine after meals, and they are well-suited for treating type 2 diabetes. Glucagon-like peptide-1 receptor agonists also lead to satiety and appetite reduction through action on the brain’s appetite regulation centers, leading to weight loss in obese patients. However, because glucagon-like peptide-1 receptor agonists work to slow gastric emptying, a safety concern has been raised in patients undergoing deep sedation or general anesthesia regarding gastric aspiration, and considering their long half-life in the blood, they are difficult to manage in the perioperative period. The purpose of this review is (i) to explore the present knowledge about the risk of aspiration before anesthesia; (ii) to describe the method for evaluating the presence of liquid and food in the stomach before surgery; and (iii) to balance the actual warning with the opportunity for future discovery about their benefits.